Analysis of Waqf Fund Collection Strategy of Dompet Dhuafa Waspada Medan - Azmi, Khairul; Siregar, Saparuddin; Rahmani, Ahmadi Bi (Borong Newinera Publisher, 2023)
This study aims to find out how the strategy of collecting waqf funds related to SWOT analysis at the Dompet Dhuafa Waspada Foundation. This study uses a qualitative approach in the form of analytical descriptive with data sourced from interviews, observations, and questionnaires. In this study, it is concluded that the SWOT analysis of the Waqf Fund Collection strategy at the Dompet Dhuafa Waspada Foundation is in the first quadrant, namely between strength (Strong) and opportunities (Opportunities), indicating that an organization is strong and has opportunities. This means that the strategy recommendations given are progressive. Strategy analysis with the SWOT method has been carried out effectively, but there are several things that need to be considered in promoting the waqf program in order to invite public interest in waqf. The need to manage waqf data accurately both in terms of collection and realization. Dompet Dhuafa Waspada must be able to see opportunities for the development of waqf in improving the economy of the people, as well as anticipate the real threat of low waqf literacy in the community. The institution presents internal training in platform management to increase the transparency of waqf funds.